The Determination Of Scaling Factor of Clay Properties - Sulaeman, Agus; Wan Hamzah, Wan Nor Hanisah; Ghazali, Amirul Hafiz (International Journal of Integrated Engineering, 2015)
The observations and tests under small scale in 1-gravity condition is intended to obtain a comparative behavior of model and prototype of geotechnical case by imposing the scaling relations. Simulation to represent related structure, sub-soil and failure mechanism need to be prepared prior to do observations in this modelling. To obtain the new parameter for sub-soil simulation and inter-dependency with scaling relationship, the ten samples with different water content of prototype clay soil were consolidated in the triaxial CU test. After consolidation, each sample were given the arbitrarily initial mean stress po =1/3 (σ1+σ2+σ3) at the same time each corresponding void ratio were recorded. The data was plotted and numbered in the e Ln p’ axises to adopt critical state line concept. Further shear stage in triaxial CU test were done to record the stress and strain of each ten samples. Among those of ten stress strain curves there were 3 similar curves (1, 6 and 8) observed when the deviatoric stress was normalized with its po, this showed similar behavior among them. The further observation revealed that void ratio in the clay soil no. 8 (ep) corresponded with void ratio of the sample no. 1 (em), stress ratio N and critical state line parameter l in the form of em= ep+ l Ln N. To support the expression of em= ep+ l Ln N, The “pile loading test” case was prepared in small scale and full scale modeling, em represented void ratio of clay in small scale and ep represented void ratio of clay at original project location. Load settlement curves were obtained from both “pile loading test” in small and full scale simulation and the result showed closely good agreement.